University software education matched to social requests - Yamaura, T.; Onoma, A.K. (1st International Symposium on Cyber Worlds (CW 2002, 2002)
We raised issues of how the software education matching to a social request should be carried out in universities in this cyber-world era. In the high-tech era, it is unavoidable that almost all the high-tech products are provided as black-box. For this reason, it, too, is unavoidable that the education in high-tech era will, in stead of extracting the befit of the high-tech stuff, force us to memorize the "manners" which were institutionalized by a few high-tech gurus. As basic tools, everybody has to learn word processors, such as Word and Ichitaro, PowerPoint and Excel, and LATEX including tgif. On the other hand, special subjects, such as programming languages, programming language theory, compiler theory, OS theory, DBMS, Internet technology, business models, and software engineering are needed when becoming a software specialist. Mathematics, such as differentiation integral calculus, and physics, such as general dynamics must be also required as liberal arts of software science. The laws related to the patent, copyright, and accountancy for a floatation, and the logical thinking method are the subjects which should be studied as an application subject. In order to prepare the educational environment to study this wide scope of subjects, we must tackle the issues such as restriction of the number of credits and maintenance of lecturer staff. Such issues may be solved by applying less strict criteria when hiring lecturers, reexamining of the whole curriculum, or changing the system of company examination when employing new hires. This paper shows some proposals and remedies applicable to the universities in Japan.